KONSEP AHLI WARIS DAN AHLI WARIS PENGGANTI: Studi Putusan Hakim Pengadilan Agama - Zuhroh, Diana (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2017)
There is a fundamental difference between the rules in Islamic inheritance jurisprudence with the rules of inheritance in the Compilation of Islamic Law. Islamic inheritance jurisprudence rules, on one hand, give inheritance rights to those who are still alive at the time of the testator died. On the other hand, the rules of inheritance in the Compilation of Islamic Law, as defined in Article 171 (c), give inheritance rights to the person who died earlier than the testator, as an attempt to legitimize